Comparison of Propofol and Sevoflurane for Laryngeal Mask Airway Insertion - Ahmeduddin Soomro, Amjad Ali,Sadqa Aftab, (Journal of Rawalpindi Medical College, 2013)
Background: To compare the hemodynamic changes, conditions for the laryngeal mask airway (LMA) insertion and time of insertion between propofol and sevoflurane. Methods: In this descriptive study sixty adult patients, scheduled for surgical procedure under general anesthesia requiring LMA insertion were included. The selected patients were allocated by balloting in two groups P and S of thirty each. Group-P received IV Propofol 2mg/kg, and Group-S was induced by sevoflurane 6-8%. The loss of eyelash reflex was considered as the desired end point for induction. Total time taken for successful LMA insertion from start of induction was noted. LMA insertion conditions were graded on a three point scale using six variables (jaw opening, ease of LMA insertion, coughing, gagging, patient movement and laryngospasm). The overall condition for LMA insertion was assessed as excellent, satisfactory or poor on the basis of total score. Results: Induction time was significantly shorter in propofol group than in the sevoflurane group. Excellent conditions for LMA insertion were noted in 93.3% patients of propofol group and 80% patients in sevoflurane group. Conditions for LMA insertion were not statistically significant between groups (p-values= 0.245). Mean arterial pressure was observed statistically significant between groups (p=0.021). Both groups showed significant drop in mean arterial pressure. There was no statistically significant difference in heart rate between groups (p=0.09). Conclusion: Propofol is superior to sevoflurane for insertion of the Laryngeal Mask Airway.